Sources of Care for Alcohol and Other Drug Problems: The Role of the African American Church - Wong, Eunice C. (Journal of religion and health, 2018)
African Americans experience significant disparities in treatment access, retention, and quality of care for alcohol and drug use (AOD) problems. Religious congregations, often the first point of contact for help with AOD problems, can play an integral role in improving access to treatment. However, little is known about the role of African American churches in addressing AOD problems. We administered a survey to a faith-based collaborative of 169 African American churches in Los Angeles to examine how AOD problems are identified in congregations, the types of support provided, barriers to providing treatment referrals, and factors associated with the provision of treatment referrals. Seventy-one percent of churches reported caring often for individuals with AOD problems. AOD problems came to the attention of congregations most commonly via a concerned family member (55%) and less frequently through individuals with AOD problems directly approaching clergy (30%). In addition to providing spiritual support, a substantial proportion of churches reported linking individuals to AOD services through referrals (62%) and consultation with providers (48%). Barriers to providing treatment referrals included lack of affordable programs (50%), stigma (50%), lack of effective treatments (45%), and insufficient resources or staff (45%). The likelihood of providing treatment referrals was greater among mid-sized versus smaller-size congregations (OR 3.43; p < .05) and among congregations with clergy that had attended seminary (OR 3.93; p < .05). Knowing how to effectively coordinate informal sources of care provided by African American churches with the formal service sector could make a significant impact on AOD treatment disparities.